A multifunctional microporous anionic metal–organic framework for column-chromatographic dye separation and selective detection and adsorption of Cr3+. Issue 46 (26th October 2015) - Zhang, Shu-Ran; Li, Jing; Du, Dong-Ying; Qin, Jun-Sheng; Li, Shun-Li; He, Wen-Wen; Su, Zhong-Min; Lan, Ya-Qian
Abstract : An anionic MOFNENU-505 exhibits selective adsorption toward cationic dyes and has been exploited for selectively sensing and adsorbing Cr 3+ for the first time. Abstract : In this work, a novel microporous anionic metal–organic framework (MOF), [Zn(ABTC)0.5 (NO3 )][(CH3 )2 NH2 ]·DMA·3H2 O (NENU-505 ; NENU = Northeast Normal University; H4 ABTC = 3, 3′, 5, 5′-azobenzenetetracarboxylic acid; DMA = N, N -dimethylacetamide), has been rationally synthesized under solvothermal conditions. Single-crystal X-ray analysis reveals thatNENU-505 is a (4, 4)-connected 3D network with pts topology. Charge neutrality is achieved by [(CH3 )2 NH2 ] + ions. It is noteworthy thatNENU-505 displays high stability in air for more than two months. In particular, the adsorption ability ofNENU-505 toward ionic dyes has been also investigated. According to the UV/vis spectroscopy analysis and the colour variance ofNENU-505, we found that the cationic dyes could be efficiently adsorbed over a period of time, while the neutral and anionic dyes could not be adsorbed. Therefore, NENU-505 exhibits selective adsorption toward cationic dyes and can potentially serve as a column-chromatographic filler for the separation of dye molecules. Furthermore, the cationic dyes can be gradually released in the presence of NaCl. More interestingly, whenNENU-505 was immersed in different metal ion DMA solutions, it performs as a rare example of a highly selective and sensitive sensor for Cr 3+ ions. In connection to this, the probable sensing mechanism was also further investigated in detail in this paper. Remarkably, this is the first MOF to exhibit an excellent ability for the detection and adsorption of Cr 3+ ions in a convenient, economical, and environmentally friendly manner.